7-DOF NONLINEAR VIBRATION ANALYSIS OF SHEARER UNDER CONDITION EXCITATION - CHEN HongYue; BAI YangXi; MAO Jun; SONG QiuShuang (Jixie qiangdu)
In order to study the influence of shearer traction speed on its dynamic characteristics,using the three-axis force of pick as the description of cutting incentive of shearer pick,Hertz contact theory was used to describe shearer’s smooth boot brace stiffness and damping. Nonlinear model of meshing gear with the clearance was used to describe brace stiffness and damping of shearer guide boot and the pin rows. 7-DOF dynamic model of shearer was established according to Lagrange ’s equations. Vibration characteristics of shearer under different traction speed was solved by numerical methods. The results show that the increasing of speed have great influence on the vibration displacement of back-end drum,have little effect on the fuselage,and have significant influence on Y axis vibration angle of the fuselage.